Estratégias do movimento estudantil nas políticas públicas de transporte na Região Metropolitana da Grande Vitória - Silva, Weslley Vitor da (2017)
The Student Movement (ME) is an important social actor in the debate on public transport policies. This work is the result of a qualitative research that aimed to understand the organic movements and demands of the students as social actors in the process of formation of public transportation policies in the Metropolitan Region of Greater Vitória (RMGV), through the use strategies. To theoretically base this research were presented concepts about public policy formation, social participation, power resources and political strategies. In order to understand the evolution of the ME flags and identify their political strategies, the primary and secondary data were collected and processed. The primary data collection was done through semistructured and secondary interviews through bibliographical and documentary research, which sought to elucidate the proposed problem of how the use of political strategies by the ME in the formation of public transport policies in the RMGV is given. After analyzes, the moments of crisis that occurred in 2011, 2013 and 2015 were identified as the background to the ME's performance. In relation to the social actors involved in public transportation policies in the RMGV, their power resources and their political strategies were identified and analyzed. It was verified that the student movement is mainly used of conflicting strategies, and that its objectives are not always reached. Therefore, from the perspective of the line of research in Operations Management in the Public Sector, which seeks to understand the importance of quality in service operations and studies the importance of planning in the public sector through project preparation, were presented as a product end of this work, propositions that indicate to the ME alternative forms of access to resources of power and use of political strategies for the empowerment of students as social actors and better effectiveness in the formation of public transport policies in the MGV.